ANALISIS PENGARUH PERTUMBUHAN EKONOMI DAN JUMLAH ANGKATAN KERJA TERHADAP JUMLAH PENGANGGURAN DI KOTA BATU - DITA NOVIA PUTRI; Sudarti Sudarti; Syamsul Hadi (Jurnal Ilmu Ekonomi JIE, 2017)
one of the factors affecting economic growth is the number of labor force and unemployment. Unemployment is one of the problems of a developing country like Indonesia. Such as Batu City which is a new autonomous region where the last few years serve as a destination city to conduct economic activities that of course affect the increase in population so that the number of unemployment impact. Therefore, the purpose of this study is: (1)To determinate how much effect of economic growth and the unemployment in the Batu City. (2)To determinate how much effect the labor force and the unemployment in Batu City. (3)To determinate which variables are most influential on the number of the unployment in the Batu City. The method of analysis in this research is multiple linier regression analysis. The result of this study indicate that: (1)Economic growth has significant effect with the number of unemployment. (2) The number of labor force has significant effect with the number of unemployment. (3)Variable of the labor force is more influential on the number of unemployment, based on the statistical F test, it was found that economic growth and the number of labor force  has significant effect with the number of unemployment.Keywords: Economic Growth, The Number of Labor Force, The Number of Unemployment